Workshop Mitigasi Bencana dalam Upaya Meningkatkan Pengetahuan, Tingkat Persepsi Risiko dan Kesiapan Individu dan Sekolah Terhadap Bencana - Taufik Hidayat, Muhamad; Puspasari, Afrin; Nurhandayani, Fitria Bekti; Ni’mah, Siti Chayatun; Mulyadi; Widhayanti, Andina (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Disaster mitigation education curriculum can increase knowledge, level of risk perception, and individual and school preparedness for disasters. Thus, it is necessary to apply it in schools, especially in disaster-prone areas. The purpose of this community service was to provide knowledge and skills for integrating disaster mitigation education into the learning curriculum in elementary school. This program was held in SD Negeri 02 Tegalmulyo and attended by 10 teachers. The method was a training program by workshop consisting of planning, implementation, and evaluation activities. The activities began with an introduction, interactive dialogue, group work, and lesson plan development. The evaluation program consists of a pre-test, a post-test, and a teacher response questionnaire. The results of the implementation showed that the community service program received a positive response from the participants. Participants considered that most of the expectations and objectives of the workshop had been fulfilled. An increase in knowledge and skills regarding the integration of disaster mitigation education into the curriculum. The teacher's response to the workshop was categorized as good. The simple lesson plan that I made was also quite good. Thus, this workshop is effective in increasing knowledge and skills related to disaster mitigation education.